Threshold Age for Doing Upper Gastrointestinal Tract Endoscopy to Screen Early Gastric Carcinoma of Bangladeshi Dyspeptic Patients: 40 years vs. 60 years - Nath, Nikhil Chandra (Mugda Medical College Journal, 2022)
Abstract not available Mugda Med Coll J. 2022; 5(1): 1-2